Temperature-dependent expression of virulence genes in Shigella species - Maurelli, A T; Blackmon, B; Curtiss, R (Infection and Immunity, 1984)
Classifications Services IAI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue IAI About IAI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy Connect to IAI IAI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0019-9567 Online ISSN: 1098-5522 Copyright © 2014 by the American Society for Microbiology. For an alternate route to IAI .asm.org, visit: IAI